PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI BUKU BESAR - HUSNAINI, NANI (JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
The aim of this research are to know the reading learning process through Big Book and are there any increase of grade B Kindergarten student capability of early reading after giving reading activities through Big Book. 14 student of grade B at Prima School Kindergarten Bekasi are the subject of this research.This research used action research method according to Kemmis and Mc. Taggart that consist of four step: a) plan, b) action, c) observation, d) reflection. The data was collected by field notes, interview, documentation and observation. The data was analyzed by qualitative and quantitative method. The result of research shows that the reading through Big Book could increase early reading capability of grade B kindergarten student. Whereas the learning process through Big Book consist of prereading, reading and after reading.Keywords: capability of early reading, big book